2013
DOI: 10.1371/journal.pone.0080006
|View full text |Cite
|
Sign up to set email alerts
|

Salmon and Human Thrombin Differentially Regulate Radicular Pain, Glial-Induced Inflammation and Spinal Neuronal Excitability through Protease-Activated Receptor-1

Abstract: Chronic neck pain is a major problem with common causes including disc herniation and spondylosis that compress the spinal nerve roots. Cervical nerve root compression in the rat produces sustained behavioral hypersensitivity, due in part to the early upregulation of pro-inflammatory cytokines, the sustained hyperexcitability of neurons in the spinal cord and degeneration in the injured nerve root. Through its activation of the protease-activated receptor-1 (PAR1), mammalian thrombin can enhance pain and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 79 publications
2
32
0
Order By: Relevance
“…BSCB permeability was investigated by immunolabeling the spinal cord for IgG, a blood protein that is not present in the CNS under normal conditions, at day 1 and day 7. Those time points were selected since they correspond to the development and maintenance of pain in this injury model (13,38-41). To investigate indicators of inflammation to pain and BSCB breakdown, serum levels of a panel of inflammatory cytokines were assayed at day 1, which corresponds to maximal BSCB breakdown.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…BSCB permeability was investigated by immunolabeling the spinal cord for IgG, a blood protein that is not present in the CNS under normal conditions, at day 1 and day 7. Those time points were selected since they correspond to the development and maintenance of pain in this injury model (13,38-41). To investigate indicators of inflammation to pain and BSCB breakdown, serum levels of a panel of inflammatory cytokines were assayed at day 1, which corresponds to maximal BSCB breakdown.…”
Section: Methodsmentioning
confidence: 99%
“…Salmon thrombin (15min+STh, n=5) or human (15min+HTh, n=4) thrombin solutions were delivered directly on top of the C7 nerve root immediately after removal of the compression (38,39,43). A control group received 20μl of NB media alone to account for the effects of the vehicle (vehicle, n=5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] Several animal models of nerve root compression have shown that even a transient, 15-minute compression applied to the nerve root is sufficient to induce sustained pain. [10, 11] In addition to pain, axonal damage and myelin degeneration are evident in the nerve root by 7 days after compression. [11] Such damage is hypothesized to relate to and cause neuronal dysfunction and contribute to the maintenance of pain by impaired axonal transport in the nerve root and disrupting the afferent signals that communicate to synapses in the spinal cord dorsal horn.…”
mentioning
confidence: 99%